Bell inequalities for entangled pairs of neutral kaons - Bramon, Albert; Nowakowski, Marek [UNESP] (American Physical Society (APS), 1999)
We extend the use of Bell inequalities to Φ → K0K̄0 decays by exploiting analogies and differences to the well-known and experimentally verified singlet-spin case. Contrasting with other analyses, our Bell inequalities are violated by quantum mechanics and can strictly be derived from local realistic theories. In principle, quantum mechanics could then be tested using unstable, oscillating states governed by a CP-violating Hamiltonian. © 1999 The American Physical Society.